The Relationship Between Discipline Indicators and The Performance of Specialist Doctors in Outpatient Services of Hospital Dr.H Kumpulan Pane, Tebing Tinggi City in 2024 - Nasution, Sumiati; Sri Melda Br. Bangun; Okto Hebron (JURNAL KESMAS DAN GIZI (JKG), 2024)
Human resources, also known as "health workers", affect the success of a hospital. Human resources consist of medical personnel such as dentists, specialist doctors, dental specialists, and subspecialist doctors, as well as non-medical personnel. Monitoring and evaluation are very necessary for the discipline specialist doctor performance in outpatient service RSUD dr.H Kumpulan Pane Tebing Tinggi. This study is quantitative study with analytical observational research type using cross-sectional study design which aims to analyze indicators of specialist doctor performance discipline in the outpatient service of RSUD. The number of samples was 37 doctors. Data collection was carried out by interviews using questionnaires and observation sheets. The independent variables are goals and abilities, leader examples, remuneration, justice and inherent supervision, while the dependent variable is specialist doctors in the outpatient service of RSUD dr.H Kumpulan Pane. Statistical tests using Chi Square ?=0.05.